Keragaman Morfologi Bakteri Nitrifikasi Asal Kompos Kotoran Domba pada Peternakan Domba dengan Sistem Bedding - Sri Martina Wiraswati; Hendro Pramono; Oedjijono; Dini Ryandini; Dyah Fitri Kusharyati; Meyta Pratiwi; Taruna Dwi Satwika; Dwiana Muflihah Yulianti; Saefuddin Aziz; Daniel Joko Wahyono; Rizal Khoirun Alfisah; Yuriza Eshananda; Budi Rustomo; Afifah Mariana (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The application of compost bedding system on sheep farm is a technology to minimize the negative impact of sheep manure waste toward environment. The microorganisms which inhabit the compost bedding, especially nitrifying bacteria are expected to have significant role in odor emission reduction which become environmental problem around the sheep farm. This study aims to analyze the abundance and diversity of nitrifying bacteria of compost bedding obtained from sheep farm which have important role in reducing odor emission of ammonia. The 12 days, 1 and 1,5 months old of compost bedding samples were obtained from sheepfold, while 3 and 4 months old of compost samples were obtained from compost pile. Furthermore, nitrifying bacteria were isolated from compost samples by pour plate method using specific media for Nitrosomonas and Nitrobacter. The results indicated that compost bedding samples with different composting time duration displayed different abundance and diversity of nitrifying bacteria. The current study was successfully isolated 39 and 47 nitrifying bacterial isolates using specific media for Nitrobacter and Nitrosomonas, respectively. The highest diversity of nitrifying bacteria was gained from 12 days old compost bedding sample. Nitrifying bacterial isolates from compost bedding samples have significant role in odor emission declining as well as manure composting at sheep farm. The obtained bacterial isolates are also potentially to develop as bio-activator for compost bedding.